Labour regulation now and in the future: Current trends and emerging themes. (April 2017) - Howe, John
This article examines recent scholarship by labour lawyers and industrial relations scholars concerning the regulation of labour markets and work relationships. Over the last two decades, scholarship in both fields has moved away from a narrow legal definition of regulation towards a more plural conception recognising the diversity of regulatory mechanisms and actors in this field. The article also charts a growth in scholarship on enforcement of labour regulation, as well as studies of the effectiveness or impact of regulation. The article suggests some key issues facing researchers of labour regulation and identifies some emerging research themes.